Efficient Sn(II)-catalyzed one-pot synthesis of a 3-substituted azetidine-2,4-dione framework - Chavan, Santosh S.; Supekar, Mrudul V.; Burate, Pralhad A.; Rupanwar, Bapurao D.; Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2017)
A novel Sn(II)-catalyzed tandem cyclization reaction of aromatic aldehydes with ethyl cyanoacetate has been achieved to afford a series of 3-substituted azetidine-2,4-diones in good to excellent yields. This protocol provides straightforward access to construct the azetidine core through sequential Knoevenagel condensation, hydration and the C-N cyclization reaction.

Triflic acid-catalyzed metal-free synthesis of (E)-2-cyanoacrylamides and 3-substituted azetidine-2,4-diones - Rupanwar, Bapurao D.; Chavan, Santosh S.; Shelke, Anil M.; Suryavanshi, Gurunath M. (New Journal of Chemistry, 2018)
A TfOH-catalyzed highly efficient synthesis of biologically active (E)-2-cyanoacrylamides and 3-substituted azetidine-2,4-diones has been reported with 64–94% yields under metal-free conditions. The reaction proceeds through sequential Knoevenagel condensation/stereoselective in situ monohydration of nitrile or C–N cyclization protocol in one-pot. The attractive features of this tandem process are moderate reaction conditions, high atom economy, broad substrate scope, gram-scale reaction and ease of operation.